2013
DOI: 10.1063/1.4793468
|View full text |Cite
|
Sign up to set email alerts
|

Diffusive hydrogen inter-cage migration in hydrogen and hydrogen-tetrahydrofuran clathrate hydrates

Abstract: Classical equilibrium molecular dynamics simulations have been performed to investigate the diffusive properties of inter-cage hydrogen migration in both pure hydrogen and mixed hydrogen-tetrahydrofuran sII hydrates at 0.05 kbar from 200 K and up to 250–260 K. For mixed H2-THF systems in which there is single H2 occupation of the small cage (labelled “1S1L”), we found that no H2 migration occurs. However, for more densely filled H2-THF and pure-H2 systems, in which there is more than single H2 occupation in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

7
66
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 56 publications
(73 citation statements)
references
References 54 publications
7
66
0
Order By: Relevance
“…10 Molecular dynamics (MD) simulations have been applied to understand the evolution of a LDA ice to a high-density amorphous ice 11,12 while considering temperature and pressure effects or to study the high-density amorphous ice/crystalline ice I h compressiondecompression at a fixed low temperature. 13 Diffusion of small molecules, in crystalline ice, [14][15][16][17][18] clathrates 18,19 and hydrates, 20 has also been studied with molecular dynamics. The previously established interstitial mechanism for He atoms in ice I h 16 has been found inappropriate for the N 2 molecules.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…10 Molecular dynamics (MD) simulations have been applied to understand the evolution of a LDA ice to a high-density amorphous ice 11,12 while considering temperature and pressure effects or to study the high-density amorphous ice/crystalline ice I h compressiondecompression at a fixed low temperature. 13 Diffusion of small molecules, in crystalline ice, [14][15][16][17][18] clathrates 18,19 and hydrates, 20 has also been studied with molecular dynamics. The previously established interstitial mechanism for He atoms in ice I h 16 has been found inappropriate for the N 2 molecules.…”
Section: Introductionmentioning
confidence: 99%
“…15 The most recent work on CO 2 diffusion in clathrates has revealed that CO 2 diffusion is possible in these solids if water vacancy exists. 18 Diffusion has also been quantified in structure materials like H 2 , tetrahydrofuran clathrate hydrates 19 or for water in cyclodextrin hydrates. 20 For a more complete insight into molecular diffusion in clathrates we recommend the very recent review by English and MacElroy 21 on molecular simulation of clathrate hydrates.…”
Section: Introductionmentioning
confidence: 99%
“…26 In both experiments, the clathrate crystal structure remained intact, demonstrating that the diffusive migration of H 2 must take place, 26 and the small cages always remained singly occupied by H 2 . [33][34][35][36] In two of these studies, 35,36 the free-energy barriers were computed for different H 2 occupancy of the neighboring large cages, and the barrier heights were found to decrease rather strongly with increasing H 2 occupancy.…”
mentioning
confidence: 99%
“…270 K) (Pefoute et al, 2012 ). At higher pressure (typically several tens of bars), studies of molecular hydrogen diffusion into THF hydrates have been performed by means of NMR method (Okuchi et al, 2007 ), in situ neutron diffraction (Mulder et al, 2008 ), volumetric measurements (Nagai et al, 2008 ), theoretical calculations (Alavi and Ripmeester, 2007 ) and molecular dynamics simulations (Cao et al, 2013 ). These measurements, performed in various P-T thermodynamics conditions, lead to diffusion coefficient ranging from ca .…”
Section: Introductionmentioning
confidence: 99%